Human Resources Development Strategy In The Post-Pandemic Covid-19 - Tuti Wediawati; Fareis Althalets; Muhammad Fikry Aransyah (Agregat: Jurnal Ekonomi dan Bisnis, 2020)
The purpose of this study is to determine the HR strategy in dealing with the COVID-19 pandemic and the new normal. HR strategy requires sensitivity to internal and external changes at the national and global levels. A qualitative phenomenology study analyzed this study. Data were collected by means of observation and interviews with several HR leaders and employees, as well as reviewing some literature. In this study, the informants were six HR managers in Indonesia. HR development is carried out in a planned and continuous manner to improve employee competence and organizational performance through policy programs that support business continuity, digitalization, health and safety. The human capital quality approach emphasizes human function as a significant determinant of organizational success in addition to financial, technological, and material capital. Then HR should be able to play a strategic role in rearranging work processes and it can be explained that three strategic functions, namely: Systemic Thinking, Corporate Culture, and Leadership. The weak ability to think systemically, corporate culture, and leadership will have implications for the ability to perform, the creativity, and sustainability of an organization is facing the era of competition and global challenges, especially during the COVID-19 pandemic.